2020
DOI: 10.3390/antiox10010016
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Microalgal DHA and Astaxanthin Affect Astaxanthin Metabolism and Redox Status of Juvenile Rainbow Trout

Abstract: Microalgal docosahexaenoic acid (DHA) and astaxanthin (AST) may substitute for fish oil and synthetic AST in aquafeeds. This study explored the effects and mechanisms of those substitutions on AST metabolism and redox status of rainbow trout fed plant protein meal (PM)- or fishmeal (FM)-based diets. Two parallel experiments (PM vs. FM) were performed with 612 juvenile rainbow trout for 16 weeks as a 2 × 3 factorial arrangement of treatments with two AST sources (synthetic (SA) vs. microalgal (AA), at 80 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Rainbow trout are the most widely utilized fish for assessing the acute toxicity of effluents. For AA and DHA, in rainbow trout, the fatal concentrations generating a 50% death rate in 96 hours (LC 50 /96 h) were 0.7-1.5 and 0.8-1.7 mL, respectively (Gregory & James, 2014;Wu et al, 2020), while in Daphnia Magna, the LC 50 /48 h values were 2.5-6.4 and 19.2 mg/L, respectively (Roy et al, 2020). Furthermore, allergic effects have been documented for AA and DHA.…”
Section: Discussionmentioning
confidence: 99%
“…Rainbow trout are the most widely utilized fish for assessing the acute toxicity of effluents. For AA and DHA, in rainbow trout, the fatal concentrations generating a 50% death rate in 96 hours (LC 50 /96 h) were 0.7-1.5 and 0.8-1.7 mL, respectively (Gregory & James, 2014;Wu et al, 2020), while in Daphnia Magna, the LC 50 /48 h values were 2.5-6.4 and 19.2 mg/L, respectively (Roy et al, 2020). Furthermore, allergic effects have been documented for AA and DHA.…”
Section: Discussionmentioning
confidence: 99%
“…Such results indicated that the pigmentation rate or astaxanthin deposition rate of the P. rhodochrous and synthetic astaxanthin is faster compared with the H. pluvialis astaxanthin. The possible reasons are as follows: (1) astaxanthin in H. pluvialis mostly exists in an esterified form, while the synthetic astaxanthin and P. rhodozyma astaxanthin mainly exist in a free form [48]; the free form of astaxanthin may be directly absorbed and accumulated in the fillet [49,50], while the esterified form of astaxanthin in the H. pluvialis needs to be decomposed before combining with fillet-related pigment cells [51,52]. (2) The green alga H. pluvialis has a cell wall, and the intracellular astaxanthin might be utilized after enzymatically breaking down for O. mykiss [6,53,54]; therefore, the breaking rate of H. pluvialis cell wall will also affect the utilization of astaxanthin in O. mykiss.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the activities of GSH-Px and SOD antioxidant enzymes’ in the plasma and liver of turbot were enhanced after dietary Nannochloropsis species supplementation [ 86 , 87 ]. The higher antioxidant capacity of NSS microalgal mixture in the present study may be attributed to their higher contents of DHA and EPA those possess excellent antioxidant properties [ 88 ]. Additionally, increasing dietary levels of omega-3 can reduce ROS production [ 80 ] via strengthening cellular ability against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%